2015
DOI: 10.1001/jamasurg.2015.1081
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Medical Costs and Use After Laparoscopic Adjustable Gastric Banding and Roux-en-Y Gastric Bypass

Abstract: IMPORTANCE There is conflicting evidence about how different bariatric procedures impact health care use. OBJECTIVE To compare the impact of laparoscopic adjustable gastric banding (AGB) and laparoscopic Roux-en-Y gastric bypass (RYGB) on health care use and costs. DESIGN, SETTING, AND PARTICIPANTS Retrospective interrupted time series with comparison series study using a national claims data set. The data analysis was initiated in September 2011 and completed in January 2015. We identified bariatric surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
4
11
0
Order By: Relevance
“…Besides, comorbidity profiles of both groups were tracked for 60 months, providing an overview of changes of comorbidities. Also, as most previous comparative cost analyses on bariatric surgery did not include exploratory analyses [20,22,36,37], this study also added current knowledge on medical costs of bariatric patients in subgroups, which allowed easy estimation of annual direct medical costs of surgical patients with different health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, comorbidity profiles of both groups were tracked for 60 months, providing an overview of changes of comorbidities. Also, as most previous comparative cost analyses on bariatric surgery did not include exploratory analyses [20,22,36,37], this study also added current knowledge on medical costs of bariatric patients in subgroups, which allowed easy estimation of annual direct medical costs of surgical patients with different health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the longer-term health care costs have shown mixed results. [4][5][6] The study in this issue of JAMA Surgery by Lewis et al 7 brings important new data to this debate. Using a unique data source, private payer claims from across the United States, the authors were able to measure health care expenditures (from the payer perspective) over time for patients undergoing laparoscopic adjustable gastric banding and laparoscopic gastric bypass procedures.…”
Section: -3mentioning
confidence: 99%
“…In many ways, this is superior to using a nonsurgical cohort of control individuals, as there is no way of knowing whether patients who do not have surgery are truly similar to those who do have surgery. The study design used by Lewis et al 7 assumes that an individual's health care spending trend will continue on a similar trajectory (a slow upward trend) if they do not have surgery, which seems quite reasonable. This study has 2 very important findings.…”
Section: -3mentioning
confidence: 99%
See 2 more Smart Citations